1991
DOI: 10.1002/tera.1420430303
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal development of cardiovascular systems in rat embryos treated with bisdiamine

Abstract: Administration of N,N'-bis(dichloroacetyl)-1,8-octamethylenediamine, bisdiamine, in pregnant Donryu rats on day 10 of gestation induces a high incidence of cardiovascular anomalies in fetuses. Bisdiamine administration induced aplasia of the sixth aortic arch artery, with both the right and left primitive pulmonary arteries being directly linked to the truncus, and resulting in four types of malformation of pulmonary arteries (PAs). When two primitive PAs shared a single root, the consequence was either pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…In the late embryonic stage, 3D reconstructed images of the bis-diamine-induced malformed hearts revealed the incomplete absorption of the sinus to the atrium as well as conotruncal anomalies such as pulmonary hypoplasia with overriding aorta and persistent truncus arteriosus, as in previous reports (Taleporos et al 1978;Kawamoto 1984;Tasaka et al 1991). These anomalies were accompanied by an abnormality of the atria, incomplete absorption of the sinus venosus and an extracardiac communication of both SVC and IVC in our experiment.…”
Section: Distribution Of Hnk-1 Immunoreactivity In Bis-diamine-inducesupporting
confidence: 68%
See 1 more Smart Citation
“…In the late embryonic stage, 3D reconstructed images of the bis-diamine-induced malformed hearts revealed the incomplete absorption of the sinus to the atrium as well as conotruncal anomalies such as pulmonary hypoplasia with overriding aorta and persistent truncus arteriosus, as in previous reports (Taleporos et al 1978;Kawamoto 1984;Tasaka et al 1991). These anomalies were accompanied by an abnormality of the atria, incomplete absorption of the sinus venosus and an extracardiac communication of both SVC and IVC in our experiment.…”
Section: Distribution Of Hnk-1 Immunoreactivity In Bis-diamine-inducesupporting
confidence: 68%
“…Administration of bis-diamine to pregnant rats induces conotruncal anomalies in the embryonic heart, and these anomalies are said to be caused by disturbance of the extracellular matrix or the migration of neural crest cells which are the precursors of the mesenchyme in the aorticopulmonary septum (Taleporos et al 1978;Kawamoto 1984;Tasaka et al 1991). There has been no report, however, concerning the changes of the conduction system in the heart with cardiovascular anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the retroesophageal right subclavian artery was formed from the right seventh intersegmental artery and a distal part of the right dorsal aorta after interrupting the proximal part, the third to seventh segments, of the right dorsal aorta Warkany 1949, 1950;Kitchell et al 1957;Okishima et al 1987;Sumida 1988;Tasaka et al 1991). In these arterial anomalous developments, recent progresses were also recognized (Bergwerff et al 1999;Molin et al 2002).…”
Section: Discussionmentioning
confidence: 89%
“…WIN, having been briefly investigated as a potential male contraceptive (Heller et al, 1961), was shown to be a potent inducer of congenital heart defects including coronary defects, yet, the cause for such defects remains poorly understood (Oster et al, 1974; Kilburn et al, 1982; Binder, 1985; Tasaka et al, 1991; Ito et al, 1992; Okishima et al, 1992; Kuribayashi and Roberts, 1993; Jackson et al, 1995; Nishijima et al, 2000; Okamoto et al, 2004; Fujino et al, 2005; Kise et al, 2005; Hanato et al, 2011). We found that administration of WIN between E9.5 and E13.5 dramatically reduced the amount of RA and alters RA-signaling in developing mouse embryos and their hearts (Wang et al, 2018).…”
Section: Resultsmentioning
confidence: 99%